Language Teaching Quality Improvement Strategies Arabic for Non Arabic Students - Ramadana (PT FORMOSA CENDEKIA GLOBAL, 2022)
Arabic is one of the foreign languages taught in schools in Indonesia, especially schools based on Islam. Arabic has its own complexity in learning, especially for those who come from schools that do not teach Arabic. So this is where a teacher is required to carry out a strategy so that the Arabic language taught does not become a scourge for students. This study aims to offer Arabic learning strategies for teachers so that they can be implemented in Arabic learning. In this study, the author uses a literature review. Data were collected from various sources related to learning strategies. Then the data were analyzed using content analysis. The results of this study found various strategies that can be used by a teacher in learning Arabic, namely, humanism-based teaching, media-based teaching, and gender-based teaching.